Taxonomic revision of the Neotropical genus Pityocera Giglio-Tos, 1896 (Diptera: Tabanidae: Scionini) - Krolow, Tiago Kütter; Henriques, Augusto Loureiro; Gorayeb, Inocêncio De Sousa; Limeira-De-Oliveira, Francisco; Buestán, Jaime (Zootaxa, 2015)
The genus Pityocera Giglio-Tos is revised based on examination of external morphology and genitalia of type material and specimens from Brazilian and foreign institutions. Five currently valid species in three subgenera are recognized: P. (Elaphella) cervus (Wiedemann, 1828); P. (Pityocera) festai Giglio-Tos, 1896; P. (Pseudelaphella) nana (Walker, 1850); P. (Pseudelaphella) nigribasis Fairchild, 1964; P. (Pseudelaphella) patellicornis (Kröber, 1930). Five new species are described: P. (Pseudelaphella) barrosi Gorayeb & Krolow sp. nov. (Brazil: Mato Grosso do Sul); P. (Pseudelaphella) gorayebi Limeira-de-Oliveira & Krolow sp. nov. (Brazil: Maranhão, Tocantins and Bahia); P. (Pseudelaphella) pernaquila Gorayeb & Krolow sp. nov. (Brazil: Pará and Rondônia); P. (Pseudelaphella) rhinolissa Krolow & Henriques sp. nov. (Brazil: Pará, Maranhão, Tocantins, Rondônia, Mato Grosso, Goiás and Mato Grosso do Sul; Bolivia: Santa Cruz); P. (Pseudelaphella) ecuadorensis Buestán & Krolow sp. nov. (Ecuador: Manabí, Guayas, Santa Elena and Loja). We provide diagnosis, descriptions, redescriptions, distribution records, illustrations and discussion for all species, as well as a key for identification of species.